Occupational Stress and Instigator Workplace Incivility as Moderated by Personality: A Test of an Occupational Stress and Workplace Incivility Model - Batista, Laura; Reio, Jr, Thomas G. (Journal of Organizational Psychology, 2019)
This research investigates the relationship between occupational stress and instigator workplace incivility, as moderated by personality, to select organizational outcomes (i.e., perceived physical health and intent to turnover). Data were collected from 206 fulltime working adults in the healthcare industry utilizing Amazon MTurk. Moderated hierarchical regressions were conducted to test the possible moderating role of personality on the stress-incivility relationship; the results demonstrated that conscientiousness and agreeableness dampened the stress-incivility relationship and neuroticism and extraversion strengthened the relationship. Hierarchical regression analyses were conducted also to explore the degree stress and incivility predicted the outcome variables of perceived physical health and intentions to turnover; the data indicated support for the notion that greater stress and incivility positively predicted turnover intent.